Las migraciones y sus consecuencias en la vida de las personas - Bustamante Mirez, Elser (2021)
This learning activity: Migrations and their consequences in people's lives, is withinthe_x000D_ development of the Social Sciences curricular area, of regular basic education, developing _x000D_ two competencies in the area; Construct historical interpretations and manage space and_x000D_ environment responsibly._x000D_ The sequence of this learning activity has taken as a basis information provided by the _x000D_ Ministry of Education, also, consulted in other bibliographic references and knowledge of _x000D_ the teaching professional experience, developed over the last years, what has been designed _x000D_ has been purpose to develop challenges in students, as well as to analyze the external and _x000D_ internal phenomena that have been occurring as a result of the Covid-19 pandemic._x000D_ In this learning activity, the competences, capacities, standards and performances ofthe area _x000D_ of Social Sciences have been taken into account, all related to what has been experienced_x000D_ recently in our country. It consists of two chapters, the first chapter supports thetheoretical _x000D_ foundation that makes it possible to understand the migratory phenomenon, the second _x000D_ chapter supports the pedagogical framework and the considerations that must be taken into _x000D_ account to develop this learning activity. _x000D_ The skills developed in this learning activity are closely related to other skills in other _x000D_ curricular areas, which have also been taken into account for the development of this activity.